Efektivitas Konseling Kelompok Dengan Teknik Rational Emotive Imagery Untuk Mereduksi Kecemasan Masyarakat Terhadap Vaksinasi Covid 19 Di Desa Muara Emburung Kabupaten Muara Enim - Putri Purmita Sari (Journal of Society Counseling, 2023)
This research is entitled "Effectiveness of Group Counseling Using Rationa Emotive Imagery Techniques to Reduce Public Anxiety Against Covid-19 Vaccination in Muara Embird Village, Muara Enim Regency.". The background of this research is marked by the existence of the Covid-19 problem which has caused the government to provide prevention in the form of vaccines to reduce Covid-19 cases. Therefore the vacci`ne causes people to experience anxiety. This study aims to describe the level of public anxiety and the effect`iveness of group counseling using rational emotive imagery techniques in reducing public anxiety about vacci`nes during the Covid-19 pandemic in Muara Embird Village, Muara Enim Regency. The method in this study is the quantitative research method with true experimental design, the research design is Pretest Posttest Control Group Design, the instruments used are questionnaires (questionnaires), and documentation. The population is 14 people and the sampling technique used is random sampling, namely 10 people. The data analysis used was the Wilcoxon test. From the results of the study describing the level of public anxiety of the 10 sample members, in general it can be obtained that 3 people are in the high category with a percentage of 22%, 6 people are in the medium category with a percentage of 60%, 1 person is in the low category with a percentage of 18%. So it can be concluded that the behavior of people's anxiety about vaccines is categorized as moderate. With the results of data analysis using the Wilcoxon test it is known that Asymp. Sig (2 tailed) has a value of 043. A value of 0.043 <0.05, it can be concluded that ha is accepted and ho is rejected, which means that there is a difference between the pretest results of the experimental group and the control group and the posttest of the experimental group and the control group. So it can be concluded that group counseling using rational emotive imagery techniques was effective in reducing people's anxiety about vaccines during the Covid- 19 pandemic in Muara Embird Village, Muara Enim Regency.